A Novel Modified Lightning Attachment Procedure Optimization Technique for Optimal Allocation of the FACTS Devices in Power Systems - Noor Habib Khan; Yong Wang; De Tian; Raheela Jamal; Sheeraz Iqbal; Mubaarak Abdulrahman Abdu Saif; Mohamed Ebeed (IEEE Access, 2021)
The Flexible AC Transmission Systems (FACTS) are the static power electronic devices that are installed and used in AC transmission networks to enhance the capability of transferring the power for providing the controllability and stability. However, the optimization of site and size of these devices is a crucial task due to their high capital cost and practical capabilities. In this paper, the optimal reactive power dispatch (ORPD) embedded with two effective controllers including the Static VAR Compensator (SVC) and Thyristor Control Series Capacitor (TCSC) is solved using a Modified Lightning Attachment Procedure Optimizer (MLAPO). The searching capability of basic LAPO is enhanced and the stagnation of basic LAPO is avoided by application of levy flight distribution and spiral orientation motion. The optimization for these devices is for reducing the power losses, voltage deviations, and the operating cost. MLAPO is examined and tested on modified IEEE30 and IEEE57 bus-standards considering SVC and TCSC. The effectiveness of MLAPO is further analyzed and compared with the outcomes of the well-known optimization techniques namely LAPO, PSO, ALO, EO, MPA, WOA and SCA with and without FACTS devices.